2022
DOI: 10.3390/nano12060945
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Radiation Response and Thermal Properties of NPs-Loaded Tissues-Mimicking Phantoms

Abstract: Many efforts have recently concentrated on constructing and developing nanoparticles (NPs) as promising thermal agent for optical hyperthermia and photothermal therapy. However, thermal energy transfer in biological tissue is a complex process involving different mechanisms such as conduction, convection, radiation. Therefore, having information about thermal properties of tissue especially when NPs are embedded in is a necessity for predicting the heat transfer during hyperthermia. In this work, the thermal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The information about the pancreas and GNR-loaded tumor properties used in our model is available in Table 1 . According to our recent experiment [ 20 ] performed on GNR-loaded agar phantom, the diffusivity of the phantom loaded with GNRs increased around 22% at a temperature of around 62 °C compared to the one at room temperature. So, in this study, we considered the average value of diffusivity from room temperature to be 62 °C [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The information about the pancreas and GNR-loaded tumor properties used in our model is available in Table 1 . According to our recent experiment [ 20 ] performed on GNR-loaded agar phantom, the diffusivity of the phantom loaded with GNRs increased around 22% at a temperature of around 62 °C compared to the one at room temperature. So, in this study, we considered the average value of diffusivity from room temperature to be 62 °C [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to our recent experiment [ 20 ] performed on GNR-loaded agar phantom, the diffusivity of the phantom loaded with GNRs increased around 22% at a temperature of around 62 °C compared to the one at room temperature. So, in this study, we considered the average value of diffusivity from room temperature to be 62 °C [ 20 ]. To estimate the refractive index (RI) of pancreas tumor loaded with GNRs, the mole fraction of pancreas tumor alone and with GNR was calculated separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the physical properties of tissues of biological origin represents a crucial aspect for several areas of biomedical engineering [1]. These areas range from the research intended to realize tissue-mimicking phantoms, i.e., materials that mimic the characteristics of biological media and are worthwhile for the testing and improvement of medical systems [2]- [6], to the characterization of tissue properties aimed at optimizing diagnostic and therapeutic procedures [7], [8]. In this regard, the study of the thermal properties of biological tissues assumes a pivotal role as these properties regulate the way heat distributes within tissue, thus, they are involved in all therapies which entail a variation of the tissue temperature to treat a disease [8].…”
Section: Introductionmentioning
confidence: 99%
“…Asadi et al evaluated the thermal response of three different NPs (black porous silicon NPs, biodegradable and excretable narrow-NIR-responsive ultrasmall-in-nano architectures, gold nanoparticles) to an 808 nm laser beam with three different powers [ 2 ]. The study found that gold nanoparticles have the highest conductivity and diffusivity and that black porous silicon-NPs have the highest radiosensitivity.…”
mentioning
confidence: 99%